2017
DOI: 10.21834/jabs.v2i3.194
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Bounded-Choice Behaviour within the Consumer of Rental Housing in Bandung, Indonesia

Abstract: The availability of choices for housing in different life phases is essential. The critical valuation from consumers becomes instrument to the quality control of housing supplied by producers. However, some consumers like students have unique characteristics, which potentially bound their housing choices. This paper describes the spatial bounded-choice phenomena from the situation of the students' behaviour in Bandung, Indonesia as a Case Study. The factual and perceptual conditions of the students' rental hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2017
2017
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
2
0
2
Order By: Relevance
“…Affluence and quality only scores mean of 4.666 while features score the mean of 4.241. Purchasers face limitations in term of limited housing options, limitation of the free flow of information between the vendors and the customers, and consumer's limited ability to assess the quality of the housing (Nurdini & Harun, 2017).…”
Section: Factors Considered In Purchasing a Housementioning
confidence: 99%
See 1 more Smart Citation
“…Affluence and quality only scores mean of 4.666 while features score the mean of 4.241. Purchasers face limitations in term of limited housing options, limitation of the free flow of information between the vendors and the customers, and consumer's limited ability to assess the quality of the housing (Nurdini & Harun, 2017).…”
Section: Factors Considered In Purchasing a Housementioning
confidence: 99%
“…Affluence and quality only scores mean of 4.666 while features score the mean of 4.241. Purchasers face limitations in term of limited housing options, limitation of the free flow of information between the vendors and the customers, and consumer's limited ability to assess the quality of the housing (Nurdini & Harun, 2017).In a study by Razak et al (2013) towards 30 property buyers in Setia Alam, Selangor Malaysia, it was found that pricing is the most important factor for house purchase with 53.3% respondents strongly concurred to it. Only 6.7% of the total respondents are neutral about the pricing factor while 40.0% of the respondents agree that the price of the property is an essential consideration in buying a house.…”
mentioning
confidence: 99%
“…Stan predstavlja prvu jedinicu društva [1], primarna je jedinica stanovanja, ali i ljudska osnovna potreba [2]. Najveća je materijalna [3] i simbolična vrijednost svakog kućanstva, te na određen način predstavlja statusni simbol [4].…”
Section: Uvodunclassified
“…Mjesto je gdje čovjek nalazi sklonište, gdje se socijalizira, obrazuje i priprema za život odraslih. Stan, ako ga promatramo kroz njegovu materijalizaciju -arhitekturu, prisutan je u svim fazama ljudskog razvoja i života [2]. Kvalitativni aspekti stanovanja dobili su na važnosti u posljednjih nekoliko godina jer su korisnici sve više svjesni problema kvalitete u stambenim okruženjima, no ne postoji puno platformi ili jednoobrazno definiranih kriterija uz pomoć kojih bi profesionalci i krajnji korisnici mogli mjeriti kvalitetu stana [7].…”
Section: Uvodunclassified